Characterisation of volatile profiles in 50 native Peruvian chili pepper using solid phase microextraction-gas chromatography mass spectrometry (SPME-GCMS) - Patel, K (2016)
The volatiles were characterised by headspace solid phase micro extraction (HS-SPME), gas chromatography mass spectrometry (GC-FID/MS). A total of 127 compounds were identified with terpenes, esters and hydrocarbons were the predominant volatile compounds. Principal component analysis (PCA) of the volatile compounds yielded 2 significant PC's, and the scatter plot generated between PC1 and PC2 successfully segregated the 50 chili pepper samples into 7 groups. Clusters of hydrocarbons, esters, terpenes, aldehyde and ketones formed the major determinants of the difference.